(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objectives: To describe and evaluate, in a formative way, an educational intervention carried out through social media on incontinence-associated dermatitis with nursing professionals from a public hospital. Method: Educational intervention study with a qualitative approach conducted in a virtual way through the social media Instagram as a platform for the dissemination of course content on the subject. Data collection was carried out with 30 nursing professionals from the medical clinic and adult intensive care unit of a public teaching hospital in the state of Mato Grosso do Sul, Brazil, between February and March 2022. Data were collected during the course and analysed through content analysis and according to Ausubel’s meaningful learning theoretical framework perspective. Results: From the analysis of the participants’ comments, four thematic categories emerged: anchoring; subordinated meaningful learning; discovery learning; and evaluation of the teaching- learning process. Conclusion: Through the results found, it was identified that the educational intervention conducted was successful in terms of sharing evidence on the subject to the participants. It was found that the Instagram can be adopted as a tool to carry out educational actions, including in a hospital environment.